Improved 1200 °C stress rupture property of single crystal superalloys by γ′-forming elements addition. (1st April 2018) - Ru, Yi; Zhang, Heng; Pei, Yanling; Li, Shusuo; Zhao, Xinbao; Gong, Shengkai; Xu, Huibin
Abstract: The 1200 °C/80 MPa stress rupture properties of single crystal superalloys are pronouncedly improved by adding γ′-forming elements Al and Ta. The fraction of γ′-precipitate at high temperature enhances with Al and Ta added. This fraction change yields the increase in concentrations of γ-strengthening elements Mo and Re in γ-channel. It produces the elevated solid solution hardening of γ-matrix and the more negative two-phase lattice misfit. The property improvement is ascribed to the increased γ′ fraction and the elevated γ solid solution level, both induced by Al and Ta addition. Graphical abstract: Image 2